RESPON PEMBUNGAAN Globba leucantha var. bicolor Holttum TERHADAP VOLUME PEMBERIAN AIR DAN PUPUK NPK GROWMORE (10:55:10) - widianty; Nurcahyo Widyo Daru Saputro; Wagiono Wagiono; Rika Yayu Agustini (Politeknik Negeri Lampung., 2021)
This study aims to determine the response of Globba leucantha plant flowering to the provision of water and NPK fertilizer. The study was conducted for 3 months September until November 2020 in a screen house located in the Dayeuhluhur sub-district, Cilacap district, Central Java. The method used was a single factor randomized design of 12 treatments repeated 3 times consisting of water and NPK fertilizer: 100% Crop Water Consumption (CWC) without fertilizer; 100% CWC fertilizer + 2 grams / plant; 100% CWC fertilizer + 4 grams / plant; 80% CWC without fertilizer; 40% CWC + fertilizer 2 grams / plant; 80% CWC + fertilizer 4 grams / plant ; 60% CWC without fertilizer; 60% CWC+ fertilizer 2 grams / plant; 60% CWC + fertilizer 4 grams / plant; 40% CWC without fertilizer; 40% CWC + fertilizer 2 grams / plant; 40% CWC + fertilizer 4 grams / plant. The results showed that the volume treatment of water and NPK fertilizer had no significant effect on the length of the panicles and the number of flowers per panicle produced.